2003
DOI: 10.1111/j.1440-1584.2003.tb00511.x
|View full text |Cite
|
Sign up to set email alerts
|

Rural Secondary School Students Living in a Small Community: Their Attitudes, Beliefs and Perceptions Towards General Practice

Abstract: Although students have very positive attitudes about general practice, the findings could be used to improve a number of GP services for young people in small rural communities. This is particularly so for presentations which require a high degree of confidentiality and skillful counselling, such as psychological problems and risk-taking behaviours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…The findings from this study complement those of previous studies on adolescent help-seeking reported in the literature, particularly barriers to communicating with adolescent boys (Atkinson et al 2003;Gleeson et al 2002;Timlin-Scalera et al 2003), and characteristics of adults preferred by adolescents seeking help in a school setting (Lindsay & Kalafat 1998). Timlin-Scalera et al (2003) also highlighted the primary focus for boys was to be seen to be 'fitting in' to their social context, and discussed how help seeking from a professional was perceived to be a sign of weakness that resulted in loss of status and respect amongst their peers.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The findings from this study complement those of previous studies on adolescent help-seeking reported in the literature, particularly barriers to communicating with adolescent boys (Atkinson et al 2003;Gleeson et al 2002;Timlin-Scalera et al 2003), and characteristics of adults preferred by adolescents seeking help in a school setting (Lindsay & Kalafat 1998). Timlin-Scalera et al (2003) also highlighted the primary focus for boys was to be seen to be 'fitting in' to their social context, and discussed how help seeking from a professional was perceived to be a sign of weakness that resulted in loss of status and respect amongst their peers.…”
Section: Discussionsupporting
confidence: 83%
“…Adolescents, particularly boys, commonly engage in risk-taking behaviors that may compromise their short-and long-term health and wellbeing. They face issues such as substance use, sexual behaviors, eating disorders, delinquency, violence, stress and depression (Barnes, Walsh, Courtney & Dowd 2004b;Quine et al 2003), the latter being a significant cause of morbidity and mortality during adolescence (Atkinson, Schattner & Margolis 2003). Viner and Barker (2005) highlighted the strong continuities between adolescent and adult health, and asserted adolescence is a critical period for engaging young people in health promoting behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Thus while valuable insights have been gained through past research, a perhaps inevitable outcome is that rural youth have become discursively constructed as 'at-risk of unsafe 3 sex' (see, for example, Atkinson, Schattner, & Margois, 2003;Hillier, Harrison, & Bowditch, 1999;Hillier, Warr, & Haste, 1998;Stewart & Rosenthal, 1997;Warr & Hillier, 1997).…”
Section: The Construction Of Rural Youth As At-riskmentioning
confidence: 99%